A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages Account must be taken of certain differences of geography and local government organisation in Scotland. For example, about 80 per cent. of Scodand's population is concentrated in about 17 per cent. of the total area of the country, across its industrial "waist." Outside the industrial belt are large, and for the most part sparsely populated, areas. Of the 55 existing health authorities in Scotland only 10 have populations of more than 100,000, and 32 have a population of under 50,000. Against this, the population of England and Wales is on the whole much more urbanised and the local government units are larger with correspondingly greater resources. There will be no substantial difference in the central machinery to be set up in Scotland as compared with England and Wales, but the arrangements proposed for the local organisation of the service will need to be modified to suit the special circumstances of Scotland. Regional Hospitals Advisory Councils In England and Wales the new joint authorities will have the dual function of administering the hospital and allied services and of planning the health service as a whole. To make a similar arrangement in Scotland would usually be out of the question. The point can best be illustrated in relation to the hospital service. Successive Committees on hospital problems have emphasised the need for planning and co-ordinating the hospital service in Scotland over wider areas and for this purpose have recommended the selection of the four natural regions based on the Cities of Glasgow, Edinburgh, Aberdeen and Dundee, where the key hospitals as well as the medical schools are to be found, with a fifth based for geographical reasons on Inverness. Although areas of this size are necessary for the planning and coordination of a comprehensive hospital service, they are clearly too large to serve as administrative units. This means that co-ordination of the hospital service and responsibility for its actual provision have in Scotland to be separated in a way which does not apply to England and Wales. Accordingly the Government propose to adopt the recommendations made by various Committees, including the Committee on Scottish Health Services and the Hetherington Committee, that a Regional Hospitals Advisory Council should be set up in each of the five regions referred to. The Council will consist of members nominated in equal numbers by the Joint Hospitals Boards of the combined local authorities in the region, described in the next paragraph, and by the voluntary hospitals, and an independent chairman will be appointed by the Secretary of State. In addition, it might include a small number of representatives of the medical and medical-educational interests of the region. The functions of the Councils will be consultative and advisory. They will advise the Secretary of State on the measures necessary to secure the co-ordination of the hospital and consultant services within the region. 24 36/H24/41